PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJARMATEMATIKA SISWA KELAS V CSDN 110 KOTA PEKANBARU - Wibowo, Arif Arif; ', Syahrilfuddin; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The background of this research is the process of learning to teach a class V C SDN 110 Pekanbaru in mathematics which still is dominated by teachers so that students become passive, as well as material provided by the teacher and the learning results are not satisfactory with an average value below the KKM.This study aims to improve student learning outcomes math class V C SDN 110 Pekanbaru. This study was conducted on 43 students. Data were collected through observation using observation sheet to the data model of problem-based learning through UH UH 1 and 2. Teacher activity increased in the first cycle the first meeting of the percentage of teacher activity 68.18%, at the second meeting into a 75.00% increase by 6.82%, the second cycle of meetings III activity increased 79.54% 4.54%, while the V meeting 88.63% increased by 9.09%. While the activities of students in the first cycle the first meeting of 61.36%, in the second meeting of the 68.18% increase of 6.82%, and the second cycle at the third meeting of 77.27%, the fourth meeting be increased by 86.36% 9:09%. Increased student learning outcomes in the first cycle than before tindakkan ie 39.53% base score of 43 students who completed the student and the first cycle to 62.79% of the 43 students who completed the students and increased by 23.26%, and the cycle II 81.39% of students who pass out of 43 students, an increase of 18.6%. From the results of research and discussion as described above that the use of problem-based learning model is correct then the activity of the teacher and student activities and student learning outcomes be improved and better. This information proves that the hypothesis which says: With the adoption of problem-based learning model can improve student learning outcomes math class V C SDN 110 Pekanbaru accepted. Keywords: Problem Based Learning, Mathematics learning outcomes.